Volumetric interpolation of tomographic sequences for accurate 3D reconstruction of anatomical parts. (October 2020) - Santarelli, Chiara; Argenti, Fabrizio; Uccheddu, Francesca; Alparone, Luciano; Carfagni, Monica
Highlights: Reconstruction of 3D anatomical models is important in several biomedical applications. Medical image sequences may be characterized by a low axial resolution. 3D reconstructions affected by staircase effect. Axial interpolation allows accurate 3D models to be obtained. Methods inspired by video processing are proposed and compared to solve the problem. Abstract: Background and objective: Tomographic sequences of biomedical images are commonly used to achieve a three-dimensional visualization of the human anatomy. In some cases, the number of images contained in the sequence is limited, e.g., in low-dose computed tomography acquired on neonatal patients, resulting in a coarse and inaccurate 3D reconstruction. Methods: In this paper, volumetric image interpolation methods, devised to increase the axial resolution of tomographic sequences and achieve a refined 3D reconstruction, are proposed and compared. The techniques taken into consideration are based on motion-compensated frame-interpolation concepts, which have been developed for video applications, mainly frame-rate conversion. Results: The performance of the proposed methods is quantitatively assessed by using sequences with a simulated low axial resolution obtained from the decimation of standard high-resolution computed tomography sequences. Real data with an actual low axial resolution have been used as well for a qualitative evaluation of the proposed methods. Conclusions: The experimental results demonstrate that the proposed methods enable an effective slice interpolation and that the achievable 3D models clearly benefit from the increased axial resolution.